Quantum Stochastic Processes, Quantum Iterated Function Systems and Entropy (São Paulo Journal of Mathematical Sciences, 2011)
We describe some basic results for Quantum Stochastic Processes and present some new results about a certain class of processes which are associated to Quantum Iterated Function Systems (QIFS). We discuss questions related to the Markov property and we present a de nition of entropy which is induced by a QIFS. This definition is a natural generalization of the Shannon-Kolmogorov entropy from Ergodic Theory.